Service Quality Towards Banking Customer Satisfaction And Loyalty PT. Bank Mandiri - Syamsul Alam; Nur Naninsih; Dewi Pratiwi Indriasari (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The research was conducted with the aim of knowing the quality of service that uses the dimensions of tangible, realibility, responsiveness, assurance and empathy for customer satisfaction and customer loyalty at PT. Bank Mandiri KC Kartini Makassar. The research population is the customers of PT. Bank Mandiri KC Kartini Makassar as many as 50,810 customers. Sampling was carried out using incidental sampling technique, using samples based on chance or incidental meeting of respondents with researchers at the research location as many as 150 customers. The data analysis method that will be used in this study is to use a structural equation model. Data analysis was performed using descriptive and inferential statistical analysis (applying Structural Equation Modeling (SEM) using the Smart PLS Version 3.0 program). The results showed that physical evidence, reliability, responsiveness, assurance, and empathy had a positive and significant impact on customer satisfaction. Meanwhile, physical evidence, reliability, responsiveness, assurance, and empathy have a positive and significant effect on customer loyalty. The management can be given a training or training for employees, so that employees are better trained to serve customers quickly. The quality of service can also affect employee performance because quality employee performance will create satisfaction with customers. Customer satisfaction can be created /formed through factors that can affect these variables such as service quality and customer loyalty.